Relationship Between Intestinal Worm Infection Soil Transmitted Helminth (STH) and Hand Washing Habits: Case Study from Second Grade Class of Children at SD Negeri 1 Sabaru Palangka Raya, Indonesia - Putri, Yasminda Liyantri; Toemon, Agnes Immanuela; Shinta, Herlina Eka; Jabal, Arif Rahman; Lestarisa, Trilianty (Manunggal Halim Jaya, 2025)
In this study, the aim was to analyse the relationship between Soil Transmitted Helminth (STH) infection and hand washing habits in grade 2 children at SD Negeri 1 Sabaru, Palangka Raya. Worm infestation is an infectious disease caused by parasites in the form of worms, especially in school-age children who are vulnerable because clean and healthy living behaviour still depends on parents.This study used an observational method with a cross-sectional design. The sample consisted of 52 grade 2 children of SD Negeri 1 Sabaru who were taken using total sampling technique based on inclusion and exclusion criteria. The examination was carried out at the Parasitology Laboratory of the Faculty of Medicine, Palangka Raya University using the Kato-Katz method. Data were analysed using the chi-square test.The results showed that the incidence of helminth infection was 15.4%. The chi-square test showed a significant relationship between hand washing habits and STH worm infections with a p value = 0.000.In conclusion, there is a relationship between Soil Transmitted Helminth (STH) intestinal worm infections and hand washing habits in grade 2 children at SD Negeri 1 Sabaru, Palangka Raya.